A cross‐sectional study comparing a blood test for methylated BCAT1 and IKZF1 tumor‐derived DNA with CEA for detection of recurrent colorectal cancer. (11th October 2016) - Young, Graeme P.; Pedersen, Susanne K.; Mansfield, Scott; Murray, David H.; Baker, Rohan T.; Rabbitt, Philippa; Byrne, Susan; Bambacas, Libby; Hollington, Paul; Symonds, Erin L.
Abstract : A novel 2‐gene (methylated BCAT1 and IKZF1 DNA) blood test was compared to CEA for detection of recurrent colorectal cancer. The methylated BCAT1/IKZF1 test was significantly more sensitive, detecting twice as many cases with recurrence. Abstract: Recurrence will develop in 30–50% of colorectal cancer (CRC) cases despite apparent clearance following treatment. Carcinoembryonic antigen (CEA) is the only guideline‐recommended blood test for monitoring cases for recurrence, but its sensitivity and specificity are suboptimal. This observational study compared a novel 2‐gene (methylated BCAT1 and IKZF1 DNA) blood test with CEA for detection of recurrent CRC. We conducted a paired comparison of the BCAT1 / IKZF1 test with CEA (cut‐off 5 ng/mL) in blood from patients in remission after treatment for primary CRC and undergoing surveillance. Blood collected in the 12 months prior to or 3 months after complete investigational assessment of recurrence status were assayed and the results compared by McNemar's test. Of 397 patients enrolled, 220 underwent satisfactory assessment for recurrence and 122 had blood testing performed within the prescribed period. In 28 cases with recurrent CRC, CEA was positive in 9 (32%; 95% CI 16–52%) compared to 19 (68%; 95% CI 48–84%) positive for methylated BCAT1/IKZF1 ( P = 0.002). All samples that were CEA positive were also BCAT1/IKZF1 positive. In 94 patients without clinically detectable recurrence, CEA was positive in 6 (6%, 95% CI 2–13%) and BCAT1/IKZF1 in 12 (13%, 95% CI 7–21%), P = 0.210. The odds ratio of a positive CEA test for recurrence was 6.9 (95% CI 2–22) compared to 14.4 (5–39) for BCAT1/IKZF1 . The BCAT1/IKZF1 test was more sensitive for recurrence than CEA and the odds of recurrence given a positive test was twice that of CEA. The BCAT1/IKZF1 test should be further considered for monitoring cases for recurrence.